Effect of a Set of Acids and Polymerization Conditions on the Architecture of Polycarbonates Obtained via Ring Opening Polymerization. Issue 9 (1st May 2017) - Jiménez‐Pardo, I.; van der Ven, L. G. J.; van Benthem, R. A. T. M.; Esteves, A. C. C.; de With, G.
ABSTRACT: Polycarbonate‐based polymers with a well‐defined architecture have become interesting materials due to their large range of applications. Ring opening polymerization (ROP) has been largely applied to make branched polycarbonates. The polymer architectures obtained via this method are strictly related with the polymerization mechanisms involved which depend on the polymerization conditions chosen. Hereby, we evaluate the catalytic activity of three acids, fumaric, trifluoroacetic, and methanesulfonic on the Cationic ROP of trimethylene carbonate (TMC) over a trifunctional initiator, trimethylol propane (TMP), under different reaction conditions. In‐detail characterization of the polymers showed the co‐existence of two polymerization mechanisms: the activated monomer (AM), which produces a tri‐armed branched polycarbonate with inclusion of the TMP initiator (TMP‐PTMC), and a combined AM/Activated Chain End (ACE) mechanism, which produces a linear polycarbonate (L‐PTMC). Such mixtures were identified for nearly all the reaction variables investigated, together with other side reactions. Upon optimization of the synthesis, the polymerizations in toluene with TFA at 35 °C and equimolar acid/initiator ratio were optimal, avoiding side reactions, but still resulting in a polymer mixture composed of ∼69% TMP‐PTMC and 31% of a polycarbonate linear polymer. The occurrence of such mixed polymer architectures is commonly overlooked in literature regarding CROP of branched polycarbonates. We demonstrate the importance of performing a full characterization for a successful detection of polymer mixtures having different (number of) end‐functionalities, which are critical for further use in advanced applications, such as in the biomedical or pharmaceutical filed. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 1502–1511 Abstract : Three acid catalysts and several polymerization conditions were evaluated in the CROP of TMC over a tri‐functional initiator, TMP. Features of the obtained polymers were characterized by NMR, GPC, and MALDI. MALDI was found an essential characterization technique to detect two polymers produced by two competitive mechanisms, which are usually overlooked when branched polymers are targeted. Metal‐free polymers with low Đ value and well‐known chemical structure and composition were synthesized, which can be further used as polymeric matrix for coating preparation or in the biomedical or pharmacological field.